Analysis of Sales Accounting Information System Implementation at PT Enigma Cipta Humanika - Nur Alimah Khasanah; Rizka Ramayanti (Sekolah Tinggi Ilmu Ekonomi Sutaatmadja, 2025)
Sales accounting information system is an information system that organizes a series of procedures and methods created in order to produce information about sales for decision making for management. This study aims to improve the effectiveness of the implementation of sales accounting information systems at PT Enigma Cipta Humanika. This research was conducted at PT Enigma Cipta Humanika. The method used in this research is descriptive qualitative. The data used is through direct interviews, observation and literature study. The analysis method used is the Miles and Huberman method. Based on the results of the study, it is found that the sales accounting information system still has weaknesses, namely in the separation of duties and responsibilities in the billing function, this is done by the finance department and the sales department. In addition, there is a lack of receipts in the talent delivery process and there is no integrated sales information system between other divisions. This can be a weakness as internal control because there is no organizational unit with integrity or internal audit that functions to ensure compliance with established procedures and to detect potential irregularities or fraud. The conclusion is that the sales accounting information system implemented is not fully effective in supporting internal control. This shows the need for system improvements, clear separation of duties, and strengthening the internal audit function so that the company's operational and financial performance can be optimized.